Influence of rare earth elements (Y, Gd and Lu) on the luminescent properties of green phosphor ZnMoO4:Tb3+. (27th November 2013) - Xu, Y.; Yang, W.; Li, X.; Li, W.; Ju, X.
ABSTRACT (Zn, Lnx)MoO4:Tb3+ (Ln = Y3+, Gd3+ and Lu3+) were prepared using the co‐precipitation method. Phase impurity, morphology and composition were investigated by power X‐ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The experimental results show that crystal structure is not destroyed after doping an appropriate amount of Y3+, Gd3+ and Lu3+. EDS analysis reveals that Y, Gd and Lu have been successfully doped into ZnMoO4. In addition, the morphology of the phosphors is notably improved, exhibiting homogeneous dispersion morphology and irregular shapes of particle size 0.5–1 µm. The luminescent intensity of (Zn, Lnx)MoO4:Tb3+ (Ln = Y3+, Gd3+ and Lu3+) phosphor is obviously higher than that of ZnMoO4:Tb3+ phosphor. The energy transfer process between trivalent rare earth ions indicates that the inert earth ions can act as an energy bridge from MoO42‐ to Tb3+. Copyright © 2013 John Wiley & Sons, Ltd.